Mapping deep endometriosis in patients with ovarian endometriomas according to the #Enzian classification: a single-center retrospective analysis - Bindra, Vimee; Naem, Antoine; Swetha, P.; Kahla, Joelle; Reddy, Archana; Laganà, Antonio Simone; Etrusco, Andrea; Andrikos, Dimitrios; Riemma, Gaetano; Agrifoglio, Vittorio; Constantin, Alin; De Wilde, Rudy Leon; et al. (Frontiers in Medicine, 2025)
ObjectiveEndometriosis is a multifactorial disease that affects mainly women of reproductive age. It is unclear whether each form of pelvic endometriosis is an independent entity and whether a spatial relationship between all three endometriosis forms exists. We aimed with this research to examine the distribution of deep endometriosis in patients with ovarian endometriomas. We also aimed to assess the influence of unilateral and bilateral ovarian endometriomas on the distribution of deep endometriotic nodules.MethodsThis is a retrospective single-center cohort study that included all patients with histologically-proven ovarian endometriomas. The #Enzian classification was used to classify endometriosis. The distribution of deep endometriosis in patients with endometriomas was assessed.ResultsA total of 106 out of 121 patients with ovarian endometriomas had coexisting deep endometriosis (87.6%). Bilateral endometriomas were more common than unilateral ones. There was a statistically significant correlation between ipsilateral ovarian endometriomas and same-sided deep endometriosis of the pelvic compartment B according to the #Enzian classification. Patients with bilateral ovarian endometriomas had deep endometriosis of the left #Enzian B pelvic compartment and rectovaginal septum at a higher frequency than patients with unilateral endometriomas.ConclusionDeep Endometriosis coexists with unilateral or bilateral ovarian endometriomas in the great majority of patients. Bilateral endometriomas are associated with higher frequencies of deep endometriosis in the left #Enzian B compartment and rectovaginal septum (#Enzian A). In order to avoid incomplete surgeries and complications, patients with endometriomas should be carefully screened for deep endometriosis of the pelvis using transvaginal ultrasound or MR imaging.